Implementasi Sistem Penyusutan Arsip di Dinas Pendidikan Provinsi Sumatera Barat - Armiati Armiati; Novia Holizah (Universitas Negeri Padang, 2019)
This study aims to find out how the activities of the assessment and depreciation of archives, constraints faced, and efforts made in overcoming the obstacles to the assessment and depreciation of records in the Education Office of West Sumatra Province. The method of this research is descriptive qualitative, with data sources of several key informants through interviews and direct observation to the object of research. Secondary data obtained from documents available at the location of the object of research. To test the validity of the data used Triangulation Technique. Based on the information from the informants, the archive assessment activities at the Office of Education in West Sumatra Province have not run optimally. It can be seen from the presence of archives that are piled up and not placed in the archive storage area. In addition, the depreciation activities in the West Sumatra Provincial Education Office were carried out in two ways, namely the transfer of archives and destruction of archives while the activities for submitting static archives to archival or ANRI institutions had not been implemented. Depreciation activities at the West Sumatra Provincial Education Office are not supplemented by documentary documents on the transfer and destruction of archives, lists of transferred files and other documents.